1957
DOI: 10.1111/j.1748-1716.1957.tb01502.x
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Low‐molecular Triglycerides.

Abstract: Summary. The LD50 of low‐molecular triglycerides has been determined by intravenous injection into mice. The triglycerides were administered in the form of emulsions. The LD50 is found to be lowest in triisovalerin (82 ± 4 mg/kg) and to increase when the fatty acid chain contains less than 5 carbon atoms, reaching 1,600 ± 81 mg/kg in triacetin. With more than 5 carbon atoms in the fatty acid chain, LD50 rises successively and lies over 10,000 mg/kg for trinonylin, tricaprinin and triunde‐cylin. With lethal dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Chem. 29,2010tions were calculated from the slope and y intercept generated by at least a three-point calibration curve. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chem. 29,2010tions were calculated from the slope and y intercept generated by at least a three-point calibration curve. …”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the melon does not serve as an energetic reserve because short-chain fatty acids are not significant sources of metabolic energy and melon lipids are of critical importance in maintaining acoustic function, and therefore should be preserved at all cost [31]. Mobilization of melon lipids is also unlikely due to its high concentrations of isovaleric acid, a fatty acid that has proven toxic when introduced into the circulation of other mammalian species [29][30][31]. In comparison, blubber lipids typically consist of longer-chain, unsaturated, straight fatty acids [36,37].…”
Section: Statistics and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of i-5:0 in the blood of patients with isovaleric acidemia causes a suite of neurological abnormalities (severe mental deficiencies, convulsions and coma), and is fatal in 50% of patients if not treated within two weeks of birth (Nyhan, 1984). Wretlind (1957) demonstrated that i-5:0 was highly toxic to mice, having a lower LD 50 compared with that of other short chains. The specific mechanisms of its toxicity are not well known, but i-5:0 is known to produce coma and EEG changes, and to inhibit mitochondrial respiration (Haas and Stumpf, 1981).…”
Section: Fatty Acids and Alcohols: The Unusual Lipid Class Constituentsmentioning
confidence: 99%
“…Rather than being produced via the sequential addition of two-carbon units in the liver, these FA are believed to be synthesized as intermediates in amino acid degradation (Morii & Kaneda 1982). i-5 : 0 is highly toxic to other mammals ( Wretlind 1957;Tanaka et al 1966), and in fact the only mammals in which this molecule is known to accumulate are human patients suffering from isovaleric acidemia, a heritable disease that can be fatal ( Tanaka et al 1966). Yet in some odontocete acoustic fats, i -5 : 0 can comprise more than two-thirds of all FA present (Koopman et al 2003(Koopman et al , 2006.…”
Section: Introductionmentioning
confidence: 99%